جدليـــــة التـاريخ و النــــص و القـاريء عند نقاد مدرسة كونستانس الألمانية - معرف, رضا (Revues faculté des lettres et des langues; No 12 (2013): مجلة كلية الآداب واللغات, 2014)
لقد صار التلقي الأدبي من أهم إنشغالات الدراسات النقدية المعاصرة ، بجعله من أهم المعايير النقدية في التعامل مع النص الأدبي، و ظاهرة التلقي هي ظاهرة قديمة مرافقة لحركة الإبداع منذ القدم ونظرا لظروف وعوامل تاريخية وسياسية واجتماعية لم يظهر التنظير لها إلا مؤخرا، وبالتحديد على يد نقاد مدرسة كونستانس الألمانية، ويعزو هذا التأخر إلى أن جل اهتمام نقاد الأدب كان منصبا إما على المؤلف أو على النص دون الالتفات إلى المتلقي بما شكل حاجزا معرفيا بين القارئ والنصوص الأدبية. ومنه اتجهت أبحاث نظرية الأدب نحو البحث في التلقي كمفهوم، وكنظرية في القراءة من أجل استجلاء معاني النص من خلال الجدلية الحوارية القائمة على العلة العلائقية بين النص ومتلقيه أو ضمن ثنائية النص/ القارئ كرد فعل على الثنائية السابقة النص/ المؤلف، وهذا كله ضمن الإطار التاريخي سواء أكان تتابعا أم تزامنا.   It has become the receive literature from the most important concerns of critical studies of contemporary, making it the most important monetary criteria in dealing with the literary text, and the phenomenon of receipt is an old phenomenon accompanying the movement of creativity since ancient times and due to the conditions and historical factors, political, social, does not appear theorizing has only recently, and specifically on the the hands of critics of the German school of Constance, and attributes this to the delay that the bulk of the attention of literary critics had focused on either the author or the text without regard to the recipient, including cognitive form a barrier between the reader and literary texts. And it tended research theory literature about research in the Receive concept, and theory in reading in order to elucidate the meanings of the text through dialectical dialogue based on reason relational between the text and its recipients or within the bilateral text / reader reaction to the previous bilateral text / author, and all this within the historical context whether or sequence coincide.